PbS QD-based photodetectors: future-oriented near-infrared detection technology. Issue 2 (5th January 2021) - Yin, Xingtian; Zhang, Cong; Guo, Yuxiao; Yang, Yawei; Xing, Yonglei; Que, Wenxiu
Abstract : With the increasing demand for near-infrared (NIR) detection in the fields of automation, military industry, communications and medical health, how to develop novel high quality and low cost NIR photodetectors has become a research hotspot in recent years. Abstract : With the increasing demand for near-infrared (NIR) detection in the fields of automation, military industry, communications and medical health, how to develop novel high quality and low cost NIR photodetectors has become a research hotspot in recent years. In order to solve the problems such as expensive raw materials, complex production equipment and difficulty in integration of traditional III–V semiconductors, PbS quantum dots (QDs) have become the most promising emerging nanomaterials for commercial NIR detection due to their excellent light absorption performance, low cost, simple deposition process and tunable band gap. This review summarizes the development strategies of PbS QD-based photodetectors over the past, focusing on the performance of devices with different structures and the feasibility of commercialization. In order to meet the needs of modern industry for NIR detection and realize commercialization, PbS QD-based photodetectors need to make breakthroughs in detection performance, device stability, device integration and large-scale preparation. These contents are discussed in detail in this paper. By comparing different strategies, the deficiencies of PbS QD-based photodetectors are proposed, and it is hoped that it can provide a reference for the further development of PbS QD-based photodetectors.